Transformative negotiation : strategies for everyday change and equitable futures - Federman, Sarah ([University of California Press], 2023)
"This book fills longstanding gaps in negotiation, a field that too often assumes everyone in diverse societies navigates the same realities. Elite solutions do not trickle down easily to those breaking cycles of poverty and disempowerment. Asking your boss for a raise at a tech company, for example, requires a different negotiation strategy than asking Social Services to help you get your kids back from the court. Context matters. This book makes central how heritage, ethnicity, wealth, gender, age, education, and other factors influence what we ask for, how people respond to our requests, as well as what is at stake when we negotiate. The same strategies used in the boardroom--if deployed in the streets--can lead to dangerous altercations. Based on the wisdom of over 100 individuals who negotiate successfully from the margins, the book provides tools for those who need them most and a guide for instructors and managers wishing to support them"--